Oxidative stress induced by chlorpromazine in patients treated and acutely poisoned with this drug - Dejanovic, Bratislav; Vuković-Dejanović, Vesna; Stevanović, Ivana; Stojanović, Ivana; Mandić Gajić, Gordana; Dilber, Sanda (Vojnosanitetski pregled, 2017)
Background/Aim. Although chlorpromazine (CPZ) is an antipsychotic drug widely used in clinical practice for a long time, its mechanism of action has not been entirely defined. An extremely difficult managing of patients acutely poisoned with CPZ is additional reason for detailed studying its toxicity mechanisms. In this clinical study, we investigated whether the oxidative stress (OS) mediates CPZ toxic effects in the exposed patients. Methods. The patients were organized into 3 groups: the T-group – hospitalized patients receiving therapeutic doses of 75–150 mg CPZ/day; the overdosed group, divided into two subgroups: the group M and the group S – mildly (CPZ serum concentration: 0.21 ± 0.05 mg/L) and severely (CPZ serum concentration: 2.66 ± 0.25 mg/L) poisoned patients, respectively, and the group C (control group of healthy volunteers). Oxidative stress parameters [total antioxidative status (TAS) and malondialdehyde (MDA) in plasma)] and superoxide dismutase (SOD) activity in erythrocytes were measured spectrophotometrically, and CPZ concentrations in serum were monitored chromatographically. One set of measurements was performed in the group C and T, whereas two sets of measurements (after 24 hours and 48 hours) were done in the poisoned patients, groups M and S. Results. A decrease of TAS and increase of SOD activity were obtained in both subgroups of the poisoned patients, compared to the controls and the group receiving therapeutic doses of CPZ. A significant increase of MDA was achieved in severely poisoned patients, compared to all other groups. Conclusion. Changed oxidative stress parameters in patients poisoned with chlorpromazine indicate involvement of oxidative stress in the toxicity mechanism(s) of chlorpromazine.